GROWTH RESPONSE OF 3 ACCESSORIES OF PORANG (Amorphophallus muelleri Blume) ON VARIATION ORGANIC FERTILIZER DOSAGE - Tini, Etik Wukir; Nisa, Khoerotun; Haryanto, Totok Agung Dwi (Jurnal Agrotek Tropika, 2025)
This study aims to examine the growth of 3 porang accessions at various organic fertilizer doses. The research is a field experiment on ex-maize land in Bobosan Village, Banyumas from September 2021 to January 2022. The treatment design was a split plot design with 2 factors. The first factor was the accession of porang consisting of 3 levels, namely the accessions of Banyumas, Madiun, and Semarang (main plot). The second factor is organic fertilizer doses consisting of 3 levels, namely 1; 1.5; and 2 kg/plant (subplot). The results showed that the Banyumas accession gave the best growth in stem diameter, plant height, and leaf area compared to the Madiun and Semarang accessions; the best fertilizer dose for porang growth has not been obtained; there is an interaction effect of fertilizer dose and porang accession on the number of leaves and plant height. Plant height and leaf number of Banyumas accessions were better at a dose of 2 kg/plant, Madiun accessions were better at a dose of 1.5 kg/plant, and Semarang accessions were better at a dose of 1 kg/plant; organic fertilizer 2 kg/plant given to the Banyumas accession produced the highest plant height and several leaves.